Volatility and tail dependence between sustainable stock indices during the COVID-19 pandemic - Janik, Bogna; Płuciennik, Piotr (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The motivation behind the study was to analyze the risk of sustainable stock indices (SSIs) and their conventional peers during the COVID-19 health crisis. We wanted to check if SSIs were more resistant to market risk in the times of huge volatility as well as what the correlation between particular SSIs was and, similarly, between their conventional peers. Aim: The main objective of the study was to analyze volatility spillover among sustainability stock indices (SSIs) and their conventional peers during the COVID-19 health crisis. The authors analyze conditional volatility among SSIs, which was obtained from univariate GARCH-type models, and the tail dependence coefficient, which was derived from the Copula-GARCH models. The indices from FTSE4Good family for the USA, Europe and Japan markets together with their corresponding conventional indices have been chosen. Results: The research shows that during the COVID-19 health crisis SSIs were less volatile than their conventional peers. Moreover the relations between particular SSIs in most cases were weaker, whereas extreme observations which occurred were less concordant for conventional indices. It implies that the stability of sustainable stock indices from FTSE4good family is greater than for their conventional peers.